2018
DOI: 10.1371/journal.pone.0205586
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of four Clostridium botulinum strains identifies proteins that link biological responses to proteomic signatures

Abstract: Microorganisms alter gene and protein expression in response to environmental conditions to adapt and survive. Whereas the genetic composition of a microbe represents an organism’s biological potential, the proteins expressed provide a functional readout of the organism’s response to the environment. Understanding protein expression patterns in response to specific environmental conditions furthers fundamental knowledge about a microbe, which can be especially useful for understudied organisms such as Clostrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Proteomic results demonstrated that the effect of growth phase was significant on protein expression in all three Y. pestis and F. tularensis strain pairs examined, a phenomenon that also has been observed in other species ( 38 ). Figure 1 shows Principal Component Analyses (PCA) of all proteomics data from Y. pestis strain pair Yp4181 (AMS) and Yp4003 (AMR, +/– antibiotics; Figures 1A,D ), F. tularensis strain pair FSC013 (AMS) and FSC016 (AMR, +/– antibiotics; Figures 1B,E ), and F. tularensis strain pair FSC201 (AMS) and FSC232 (AMR, +/– antibiotics; Figures 1C,F ).…”
Section: Resultssupporting
confidence: 69%
“…Proteomic results demonstrated that the effect of growth phase was significant on protein expression in all three Y. pestis and F. tularensis strain pairs examined, a phenomenon that also has been observed in other species ( 38 ). Figure 1 shows Principal Component Analyses (PCA) of all proteomics data from Y. pestis strain pair Yp4181 (AMS) and Yp4003 (AMR, +/– antibiotics; Figures 1A,D ), F. tularensis strain pair FSC013 (AMS) and FSC016 (AMR, +/– antibiotics; Figures 1B,E ), and F. tularensis strain pair FSC201 (AMS) and FSC232 (AMR, +/– antibiotics; Figures 1C,F ).…”
Section: Resultssupporting
confidence: 69%
“…For example, Deatherage Kaiser et al. [ 41 ] studied the reproducibility of bacterial protein profile patterns using Clostridium botulinum as a study system. The effect of bacterial strain, culture medium, and the growth phase on protein expression profiles was determined using LC and TMS.…”
Section: Molecular Methods In Studying Microbesmentioning
confidence: 99%
“…Culture filtrates were concentrated using 10 kDa cutoff membranes (Millipore, USA) and precipitated using 10% Ice-cold trichloroacetic acid (Sigma USA) after that incubated on ice for 3 h. Precipitate were centrifuged at 8000× g for 30 min at 4 °C and washed the pellet three times with cold acetone and left the room for air dried (Hirose et al 2000 ). Further, the pellets were resuspended in protein solubilization buffer (8 M urea, 2% CHAPS, and 2% carrier ampholytes pH 4–7) (Deatherage Kaiser et al 2018 ). The resultant proteins were cleaned using protein clean up kit (Bio-Rad, USA).…”
Section: Methodsmentioning
confidence: 99%